PENGARUH PROPORSI SERBUK JAHE DAN KOLAGEN TERHADAP SIFAT FISIK DAN DAYA TERIMA MINUMAN HERBAL UNTUK KESEHATAN DAN KECANTIKAN KULIT - winda tri lestari Lestari; Maspiyah Maspiyah; Novia Restu Windayani; Octaverina Kecvara Pritasari (Jurnal Tata Rias, 2026)
Skin health and beauty are important aspects closely related to appearance and self-confidence. This investigation is designed to evaluate the impact of the proportion of ginger powder and collagen on sensory attributes and acceptability of a functional herbal beverage for skin health and beauty. The study employed an experimental method with three formulations, namely 60:40, 70:30, and 80:20 ratios of ginger powder to collagen. Organoleptic testing was conducted by 30 panelists using a Likert scale with parameters including aroma, taste, color, and overall preference. The gathered metrics were evaluated via descriptive statistics, OneWay ANOVA, along with Duncan’s multiple range test. The findings indicated that the proportion of ginger powder and collagen exerted a profound influence across all measured variables (Sig. < 0.05). The most superior combination was identified at the 80:20 ratio, which secured the peak ratings regarding scent, flavor, appearance, and general acceptability. Consequently, this specific blend is deemed highly ideal, favorably received by the assessors, and possesses the prospective capacity to be manufactured into a functional herbal beverage that promotes skin health and beauty.